Socialization and Simulation of Stunting Prevention through Youth Posyandu: Case Study of Lembang Village, Garut - Nur Annisa, Yulia; Pratiwi, Nisa; Indriani, Mirna; Amelya Putri, Puput; Sabela, Mila; Gusti Utami, Widi; Yuliyanti, Ninda; Puspita Amelia, Vira; Fazri, Ahmad; Abdurahman, Ziyad; Rasyiid H, Javier (International Journal of Transdisciplinary Knowledge, 2024)
This community service aims to prevent stunting since adolescence through comprehensive health education and services. The benefits include increasing adolescents’ awareness of the importance of health and their readiness to become healthier individuals, ultimately contributing to the creation of a stunting-free generation in the future. The method used was qualitative with a descriptive approach. The data collection techniques used include observation, interviews and documentation studies. The results of this community service show that the socialization and simulation of stunting prevention through youth posyandu which includes providing education and innovating 6 youth services are expected to be implemented optimally in Lembang Village, Garut. The six services include health education, psychological counseling services, health services and nutrition counseling, interests and talents, self love, services and education on adolescent sexual reproductive health.